Build Competitive Advantage to Improve Company Performance - HENDRAYANTI, SILVIA (Universitas Negeri Semarang, 2022)
The development of the pharmacy business is driven by the growth of market opportunities resulting in fierce competition between pharmacies, every pharmacy business is required to create a good and integrated competitive strategy to win business competition. This study aims to find out how a company can win the competition and improve company performance. In this study using several variables including: Environmental Adaptability, differentiation strategy, efficiency strategy, competitive advantage, company performance.This study used a sample of 118 respondents and processed using the Structural Equation Model (SEM) analysis technique.The results show that environmental adaptability has a positive effect on differentiation strategy, environmental adaptability has a positive effect on efficiency strategy,differentiation strategy has a positive effect on competitive advantage, efficiency strategy has a positive effect on competitive advantage, competitive advantage has a positive effect on company performance.Future research is expected to reveal things that have not been answered in this study so that it will complement the findings of previous studies. For example, by adding several indicators or variables that have not been included in this study, which can be included in further research, so that by including many variables in this study more valid results will be obtained